Penerapan Teknik Shadowing dalam Kegiatan Menyimak Bahasa Jepang pada Siswa Kelas X SMA - Lusi Asmaraningtyas; Ina Ika Pratita; Miftachul Amri (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Listening is the most basic skill in language learning. A voice that cannot be heard, cannot be pronounced properly. If you don't understand what the other person is saying, then you can't participate in communication. The purpose of this study was to find out the results of the application of the Shadowing learning model in listening to Japanese learning activities for class X students at SMAN 5 Malang, specifically focusing on Chouon (long vowel) with the theme "Self Introduction/Jikoshoukai". The number of participants was 22 students of class X specializing in language. The instrument used is Pre-Test Post-Test in the form of multiple choice questions and fill in gaps in sentences. The data analysis technique used a comparative hypothesis test or comparison test. The results of this study were, the average value of the pre-test (before treatment) was 36.2 and the average value of the post-test (after treatment) was 62.5. From these results, it can be concluded that the implication of the shadowing technique as one of interactive methode in learning language, can improves students' listening skills, especially the ability to distinguish long and short forms of Japanese words.